Transect Analysis of Orographic Precipitation in the Mount Rinjani Region: Case Study of the Sembalun Valley - Pamungkas, Cakra Mahasurya Atmojo; Maulidita, Ummi; Maurits, Yuhanna; Putrantijo, Nuga (Indonesian Journal Publisher, 2025)
Rainfall distribution in mountainous regions is powerfully shaped by orography, yet detailed spatial understanding in Indonesia remains limited. This study examines orographic precipitation patterns and rain-shadow effects on Mount Rinjani using two main transects, west–east (WE) and north–south (NS), intersecting the Sembalun Valley. As a representative leeward site, Sembalun is the focal point of analysis, with attention to rainfall variability across timescales and the occurrence of extreme events. Daily rainfall data ( 1 km resolution) from CHELSA-W5E5, spanning 1979–2016, were analysed. Results reveal sharp contrasts between windward and leeward slopes. Along the WE transect, rainfall rises toward the summit and declines steeply eastward into Sembalun, producing a structured leeward gradient of 22.6 mm per 100 m compared with a more variable 9.0 mm per 100 m on the windward side. Seasonal analysis highlights December–February as the peak rainfall period due to orographic enhancement, whereas shifting monsoonal winds shift the positions of the windward and leeward slopes along the NS transect. Extreme event analysis reveals that over 38 years, more than 25 days exceeded 50 mm on the western slope, while the east recorded far fewer. These findings confirm classical orographic uplift theory while demonstrating its modulation by monsoonal circulation in a tropical island context. They underscore the role of topography in shaping both overall rainfall patterns and precipitation extremes, with implications for hazard risk, irrigation, and tourism in Sembalun. The study provides a scientific basis for climate adaptation, water conservation, and sustainable land-use in the Rinjani region.